Lattice Boltzmann Simulation of Steady Flow in a Semi-Elliptical Cavity (Communications in Computational Physics, 2018)
The lattice Boltzmann method is employed to simulate the steady flow in atwo-dimensional lid-driven semi-elliptical cavity. Reynolds number (Re) and vertical-to-horizontalsemi-axis ratio (D) are in the range of 500-5000 and 0.1-4, respectively.The effects of Re and D on the vortex structure and pressure field are investigated,and the evolutionary features of the vortex structure with Re and D are analyzed indetail. Simulation results show that the vortex structure and its evolutionary featuressignificantly depend on Re and D. The steady flow is characterized by one vortex inthe semi-elliptical cavity when both Re and D are small. As Re increases, the appearanceof the vortex structure becomes more complex. When D is less than 1, increasingD makes the large vortexes more round, and the evolution of the vortexes with D becomesmore complex with increasing Re. When D is greater than 1, the steady flowconsists of a series of large vortexes which superimpose on each other. As Re and Dincrease, the number of the large vortexes increases. Additionally, a small vortex inthe upper-left corner of the semi-elliptical cavity appears at a large Re and its size increasesslowly as Re increases. The highest pressures appear in the upper-right cornerand the pressure changes drastically in the upper-right region of the cavity. The totalpressure differences in the semi-elliptical cavity with a fixed D decrease with increasingRe. In the region of the main vortex, the pressure contours nearly coincide with thestreamlines, especially for the cavity flow with a large Re.